(untitled) (Research, Society and Development, 2022)
Titanium, when kept at ambient atmosphere and room temperature, generates a thin and adherent oxide layer (TiO2) which promotes corrosion restance. Due to this characteristic, the anodizing of titanium has been studied for biomedical applications, but despite excellent biocompatibility, titanium prostheses can generate implant-associated infections. The literature describes the incorporation of silver nanofillers (AgNPs) on the titanium surface, increasing the material’s antimicrobial activity and, consequently, reducing the occurrence of infections. Thus, the objective of this work was to identify the most suitable process for incorporation of silver nanofillers on the anodized titanium surface. In this sense, titanium samples were (i) anodized in aqueous citric acid containing silver nitrate (AgNO3), (ii) anodized in aqueous citric acid and subsequently immersed in an aqueous solution of Psidium guajava extract + AgNO3 and (iii) anodized in H2SO4 + H2O2 followed by sealing process conducted in solution containing Psidium guajava extract + AgNO3. Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS) analysis were performed to verify the efficiency of incorporation of the nanofillers by each method. The results showed to be possible incorporate AgNPs over titanium oxide through the process (i) anodization in citric acid + AgNO3 and (iii) anodization in H2SO4 + H2O2 and sealing in solution containing plant extract + AgNO3. Furthermore, potentiodynamic polarization and cytotoxicity trials were performed on samples from process (iii) and revealed that the incorporation of AgNP’s improves the corrosion resistance and favors the antimicrobial effect of the sample’s surfaces.